Pengaruh self-efficacy dan emotional-regulation terhadap kecemasan pertunjukan musik pada paduan suara mahasiswa Universitas X - Akbar Lindo Pratama; Novia Solichah (UIN Maulana Malik Ibrahim Malang, 2022)
ABSTRACTMusic performance anxiety is an anxiety experienced by a musician when he is in a performance. The feeling of anxiety or stage fright is naturally felt by musicians when they are about to perform a performance, but if this happens continuously it will disturb and make musicians lose focus. Even when musicians are unable to handle the pressure, musicians will fall prey to narcotics and commit suicide. Therefore the need for a musician to prevent the occurrence of MPA. What can help prevent MPA symptoms is self-efficacy and emotional regulation. This research method uses a quantitative research method with multiple regression types. The measuring tools used in this study were the General Self-Efficacy Scale (GSE), Emotion Regulation Questionnaire (ERQ), and Music performance anxiety Inventory Adolescent (MPAI-A). The subjects in this study were 68 singers. Analysis of the research data using SPSS 25.0 for Windows.The results showed that self-efficacy and emotional regulation had an effect of 15.8% on music performance anxiety with a sig value of 0.004 0.05. So that hypothesis can be accepted. Self-efficacy makes an effective contribution of 13.2% and emotional regulation provides an effective contribution of 2.6%.KEY WORDS : self efficacy; regulation emostion; music performance anxiety; choirABSTRAKMusic performance anxiety merupakan sebuah kecemasan yang dialami oleh seorang musisi ketika berada dalam sebuah pertunjukan. Rasa cemas atau demam panggung tersebut wajar dirasakan musisi ketika akan menampilkan sebuah pertunjukan, namun jika hal tersebut terjadi secara terus menerus akan mengganggu dan membuat musisi kehilangan fokus. Bahkan ketika musisi tidak mampu mengatasi tekanan, musisi akan terjerumus pada narkotika dan bunuh diri. Oleh karena itu perlunya seorang musisi mencegah terjadinya MPA. Beberapa hal yang dapat mencegah MPA ialah efikasi diri dan regulasi emosi. Metode penelitian ini menggunakan metode penelitian kuantitaitf dengan jenis regresi berganda. Alat ukur yang digunakan dalam penelitian ini adalah General Self-Efficacy Scale (GSE), Emotion Regulation Questionnaire (ERQ), dan Music performance anxiety Inventory Adolescent (MPAI-A). Subjek pada penelitian ini berjumlah 68 singer. Analisis data pada penelitian ini menggunakan bantuan program SPSS for windows 25.0. Hasil penelitian menunjukan efikasi diri dan regulasi emosi memiliki pengaruh sebesar 15,8% terhadap music performance anxiety dengan nilai sig 0,004 0,05. Sehingga hipotesis dapat dapat diterima. Efikasi diri memberikan sumbangan efektif sebesar 13,2% dan regulasi emosi memberikan sumbangan efektif sebesar 2,6%.KATA KUNCIefikasi diri; regulasi emosi; music performance anxiety; paduan suara Copyright ©2022. The Authors. Published by JIPS: Journal of Indonesian Psychological Science. This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0